Adsorption Equilibrium and Kinetics of the Removal of Ammoniacal Nitrogen by Zeolite X/Activated Carbon Composite Synthesized from Elutrilithe - Yong Zhang; Feng Yu; Wenping Cheng; Jiancheng Wang; Juanjuan Ma (Journal of Chemistry)
Zeolite X/activated carbon composite material (X/AC) was prepared from elutrilithe, by a process consisting of carbonization, activation, and subsequent hydrothermal transformation of aluminosilicate in alkaline solution, which was used for the removal of ammoniacal nitrogen from aqueous solutions. Adsorption kinetics, equilibrium, and thermodynamic were studied and fitted by various models. The adsorption kinetics is best depicted by pseudosecond-order model, and the adsorption isotherm fits the Freundlich and Redlich-Peterson model. This explains the ammoniacal nitrogen adsorption onto X/AC which was chemical adsorption in nature. Thermodynamic properties such as ΔG, ΔH, and ΔS were determined for the ammoniacal nitrogen adsorption, and the positive enthalpy confirmed that the adsorption process was endothermic. It can be inferred that ammoniacal nitrogen removal by X/AC composite is attributed to the ion exchange ability of zeolite X. Further, as a novel sorbent, this material has the potential application in removing ammoniacal nitrogen coexisting with other organic compounds from industrial wastewater.